Case Report: External Drainage Procedure in Pediatric Pancreas Pseudocyst - Halim, Freda Susana (Medicinus, 2021)
Introduction: Pediatric pseudocyst of the pancreas is a rare condition. The therapy given in such a case is usually conservative while waiting for the pseudocyst wall to become mature and followed by an internal drainage procedure. The purpose of this report is to prove that external drainage of such cases is safe and will help to enhance patient recovery.Case Illustration: 4 y.o. boy comes to ER with a chief complaint of epigastric pain with minimal nausea and vomiting, after blunt abdominal trauma 12 hours previously. The primary survey was normal and stable. A bit of distension is found in the abdomen with tenderness and rebound tenderness without muscular rigidity. Free fluid was found but no active bleeding from solid and hollow abdominal organs in abdominal USG. A similar finding was found in Abdominal CT with IV Contrast. After 6 days of hospitalization, feeding becomes a serious problem as abdominal distention is progressing and liquid food is intolerable.Â Method/Therapeutic Intervention: Exploration by laparoscopy cannot be done due to the unavailability of laparoscopic tools, then laparotomy was done. Pancreas pseudocyst was found, and external drainage is done.Result: After an operation, dramatic progression of the patient's condition is observed. Feeding tolerance is improving and on the 4th day after the operation, the patient came. In the follow-up period, 1 month after operation the drain was released and no sign of pancreatic leakage was found within a one-year post-operative period.Â Conclusion: External drainage could be considered in pediatric pseudocyst pancreas if the feeding problem is prominent.